1996
DOI: 10.1021/jp952859m
|View full text |Cite
|
Sign up to set email alerts
|

Formic Acid Oxidation on Ultrathin Pd Films on Au(hkl) and Pt(hkl) Electrodes

Abstract: The oxidation of formic acid on thin, epitaxially-grown Pd overlayers on Au and Pt single crystal electrodes was studied as a function of overlayer thickness ranging from submonolayer coverages up to the equivalent of 10 monolayers. The results were compared with those for massive Pd single crystal surfaces. The electrocatalytic properties of the Pd overlayers were found to depend markedly on their thickness and on their crystallographic orientation. Pd(100) showed the highest catalytic activity of all three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
299
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(329 citation statements)
references
References 41 publications
25
299
0
5
Order By: Relevance
“…Kolb et al demonstrated that the electrocatalytic activity of Pd overlayers on Au and Pt single crystal electrodes depends markedly on their crystallographic orientation; following the trend Pd(111) < Pd(110) < Pd(100) [15,16]. Although in previous studies the same authors showed that the activity of Pd nanostructures towards HCOOH oxidation is enhanced in the presence of a carbon support, leading to lower deactivation kinetics under potentiostatic conditions [13,14,17];…”
Section: Introductionmentioning
confidence: 99%
“…Kolb et al demonstrated that the electrocatalytic activity of Pd overlayers on Au and Pt single crystal electrodes depends markedly on their crystallographic orientation; following the trend Pd(111) < Pd(110) < Pd(100) [15,16]. Although in previous studies the same authors showed that the activity of Pd nanostructures towards HCOOH oxidation is enhanced in the presence of a carbon support, leading to lower deactivation kinetics under potentiostatic conditions [13,14,17];…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it is still desirable to increase the number of liquid fuels that can be employed in these systems in order to extend the practical application of low-temperature fuel cells and to facilitate their penetration into energy market. Besides methanol, other small organic compounds such as formic acid [7][8][9][10][11], formaldehyde [9,11], ethanol [12], ethylene glycol [12,13], n-propanol [12] and so on have been investigated and demonstrated appropriate for this type fuel cell, because they are reasonably inexpensive, nontoxic and largely available and have suitable electrochemical reactivity at relatively low temperatures. Furthermore, they have comparable energy density and reversible energy efficiency compared to H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Only shortly after the successful UHV studies, the adsorption and catalytic properties of pseudomorphic Pd films supported on single crystal metal surfaces has also received considerable attention in the field of surface electrochemistry [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%